2020
DOI: 10.18632/oncotarget.27647
|View full text |Cite
|
Sign up to set email alerts
|

Development and comprehensive characterization of porcine hepatocellular carcinoma for translational liver cancer investigation

Abstract: Hepatocellular carcinoma (HCC) is the second leading cause of cancer-related death worldwide. New animal models that faithfully recapitulate human HCC phenotypes are required to address unmet clinical needs and advance standard-of-care therapeutics. This study utilized the Oncopig Cancer Model to develop a translational porcine HCC model which can serve as a bridge between murine studies and human clinical practice. Reliable development of Oncopig HCC cell lines was demonstrated through hepatocyte isolation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
(22 reference statements)
1
20
0
Order By: Relevance
“…Recently published data has also shown the oncopig tumor holds a heterogeneous population of tumor hepatocellular carcinoma cells. The results indicate the presence of intratumor heterogeneity resulted from the accumulation of somatic mutations in distinct tumor cells as commonly observed in human HCC (Gaba et al, 2020). Finally, the OCM showed that expression of TP53 R167H and KRAS G12D generated tumors that recapitulated transcriptional characteristics found in human soft tissue sarcomas (Schachtschneider et al, 2017a).…”
Section: Perspective: Humanized Swine Models Of Bcmentioning
confidence: 62%
“…Recently published data has also shown the oncopig tumor holds a heterogeneous population of tumor hepatocellular carcinoma cells. The results indicate the presence of intratumor heterogeneity resulted from the accumulation of somatic mutations in distinct tumor cells as commonly observed in human HCC (Gaba et al, 2020). Finally, the OCM showed that expression of TP53 R167H and KRAS G12D generated tumors that recapitulated transcriptional characteristics found in human soft tissue sarcomas (Schachtschneider et al, 2017a).…”
Section: Perspective: Humanized Swine Models Of Bcmentioning
confidence: 62%
“…Second, although TP53 driver mutations are commonly observed in clinical HCC, the KRAS driver mutation is rarely observed in HCC ( Hussain et al, 2007 ; Turhal et al, 2015 ). However, previous publications have demonstrated that Oncopig HCC recapitulates human HCC in terms of transcriptional profiles, histological phenotypes, AFP expression, proliferation rates, migration rates, and chemotherapeutic susceptibilities ( Schachtschneider et al, 2017a ; Gaba et al, 2020 ). Therefore, despite the presence of a KRAS driver mutation, the Oncopig HCC model represents a clinically relevant large animal HCC model.…”
Section: Discussionmentioning
confidence: 99%
“…Primary hepatocytes were isolated and transformed into HCC cells from Oncopig liver tissues ( n = 2 female, n = 1 male) as previously described ( Schachtschneider et al, 2017a ; Gaba et al, 2020 ). Briefly, primary hepatocytes were isolated from resected Oncopig liver tissues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The medium was changed to DMEM containing 10% FBS at 4 h post-transduction. Expression of the transgene and hepatocellular origin of the cells were confirmed by RT-PCR and arginase-1 staining, respectively, as previously described [4,5].…”
Section: Generation Of Porcine Hcc Cellsmentioning
confidence: 99%